News Stream Summarization using Burst Information Networks - Ge, Tao; Cui, Lei; Chang, Baobao; Li, Sujian; Zhou, Ming; Sui, Zhifang (EMNLP 2016, 2016)
This paper studies summarizing key information from news streams. We propose simple yet effective models to solve the problem based on a novel and promising representation of text streams – Burst Information Networks (BINets). A BINet can be aware of redundant information, allows global analysis of a text stream, and can be efficiently built and dynamically updated, which perfectly fits the demands of text stream summarization. Extensive experiments show that the BINet-based approaches are not only efficient and can be used in a real-time online summarization setting, but also can generate high-quality summaries, outperforming the state-of-the-art approach.